Empirical study of the reverse-causality between organisation performance and employee behaviour in the agricultural manufacturing sector of Malawi - Mvula, Ronnie Timpuza (My University, 2018)
Many organisations claim that Human Resources are their critical resource. However, what is most critical is not merely the human resources but how the Human Resources are managed. Human Resource Management is achieved through practices that the firm implements; these give the firm sustained competitive advantage. Many studies have found positive and significant relationship between HR management and firm performance. Previous studies have also studied reverse causality investigating whether organisational performance affects HR management policies and found significant positive relationship implying that it is good performing organisations that can afford adopting HRM practices. The purpose of this study was to investigate whether organisational performance motivates how employees behave at work in the reverse causality in the agricultural manufacturing firms in Malawi. To achieve this purpose a survey design was adopted using quantitative research strategy. Data were collected from a probability sample of 77 managers and 308 employees totalling 385 participants. Descriptive and inferential statistics using Structural Equation Modelling (SEM) were used to analyse and test seven hypotheses. The proposed relationships were tested using a number of statistical methods. Adequate reliability was achieved on all measurement scales. Confirmatory factor analysis was conducted on the content and structure of the measured constructs and were confirmed necessary. Reasonable fit was achieved for all the refined measurement models. A Lisrel based SEM was applied to examine whether the model fitted the data obtained from the sample and test the relationships between latent variables. Consistent with previous research; results of SEM revealed that Human Resource Management (HRM) practices are significant correlates of organisational performance. Further results showed positive relationships between business strategy and HRM practices; HRM practices and organisational performance. Significant negative relationship was found between employee attitudes and employee behaviour and employee behaviour and organisational performance.
Dissertation submitted to the School of Economic & Business Sciences in fulfilment for the requirements of award of the degree: PhD Business Sciences (Human Resources Management) in the Faculty of Commerce, Law and Management, University of the Witwatersrand.
Keywords: Organizational effectiveness; Organizational learning